A leadership education framework addressing relationship management, burnout, and team trust. Issue 2 (3rd April 2019) - White, Bobbie Ann Adair; Bledsoe, Christie; Hendricks, Randy; Arroliga, Alejandro C.
Abstract: Despite the collaborative nature of medicine, most medical professionals are not taught or trained to lead collaboratively. Even when leadership skills and content are incorporated into the curriculum, rarely is the content focused on relationship management and trust, both of which are imperative to collaborative and team leadership in medicine. Resonant leadership is a leadership framework centered on emotional and social intelligence. Emotional intelligence, a concept involving skills that can be taught and improved, has proven to be important in leadership. Resonant leaders, or leaders with social and emotional intelligence, develop positive relationships and environments, engaging team members to work toward a common goal through mindfulness, hope, and compassion. This article examines the current state of leadership education and development and proposes resonant leadership as a viable framework for education. A leadership framework heavy on emotional and social intelligence is ideal for the team environment of medicine, and there is literature to back up the positive outcomes of leading with this framework in a clinical setting, including reduction of burnout, building team trust, and better relationship management.